Maternal-fetal immunologic response to SARS-CoV-2 infection in a symptomatic vulnerable population: A prospective cohort - Larcade, Ramon (2021)
Background: COVID-19 disproportionally affects pregnant women and their newborn, yet little is known about the variables that modulate the maternal-fetal immune response to infection.Methods: We prospectively studied socioeconomic, biologic and clinical factors affecting humoral immunity in 87 unvaccinated pregnant women admitted to hospital in the Buenos Aires metropolitan area for symptoms consistent with COVID-19 disease.Results: The number of days between symptom onset and childbirth predicted maternal and newborn virus Spike protein Receptor Binding Domain (RBD)-specific IgG. These findings suggest newborns may benefit less when mothers deliver soon after COVID-19 infection. Similarly, a longer time between symptom onset and birth predicted higher in utero transfer of maternal IgG and its concentration in cord blood. Older gestational ages at birth were associated with lower maternal IgG: cord blood IgG ratios. Eighty seven percent of women with confirmed SARS-CoV-2 infection developed RBD-specific IgA responses in breast milk within 96 h of childbirth. IgA was not significantly associated with time from infection but correlated with maternal serum IgG and placental transfer.Conclusions: These results demonstrate the combined role of biologic, clinical and socioeconomic variables associated with maternal SARS-CoV-2 RBD-specific antibodies and supports early vaccination strategies for COVID-19 in socioeconomically vulnerable pregnant women.